The older person's experience of autonomy in healthcare decision-making in Ireland: The relationship between law, policy, and practice. (December 2022) - Lombard, John; Davidson, Hope
The law on healthcare decision-making in Ireland is in a period of transition and will be enhanced with the full commencement of the Assisted Decision-Making (Capacity) Act (ADMC Act) 2015. The legislation is intended to empower a person to make decisions relating to their healthcare and personal affairs where they lack or may in the future lack the capacity to make their own decisions. This is especially relevant for the older person in terms of planning for future healthcare decisions. This article reports on quantitative and qualitative research which examined the exercise of autonomy by the older person in Ireland in the context of healthcare decision-making. The research compared the lived experience of healthcare decision-making with the existing legal and policy framework. The research sought to identify what is currently understood about the ADMC Act and awareness of the changes it will bring about in decision-making for the older person. These data assist in identifying strengths, such as a feeling of involvement, and weaknesses, such as an asymmetry of information, in the operation of the current decision-making framework while also identifying potential hurdles to the meaningful implementation of the 2015 Act.